Joining Forces with Veterans: Veterans' and Researchers' Perspectives on Veteran-Centered Engagement Practices - David Hibler; Cheryl A. Krause-Parello; Brian Gliba; James Morris; C. Daniel Mullins (The University of Alabama, 2023)
Community-engaged research must reflect the uniqueness of the specific community involved. To help researchers produce quality community-engaged research with the veteran community, the authors of this paper (a coalition of both veterans and academic researchers) have highlighted essential considerations when engaging the veteran community in the research enterprise. Research with veterans requires unique sensitivity based on the impacts of their military service, history, and experiences. Understanding the impacts of veteran culture and community on recruitment is an essential prerequisite for anyone engaging with this population. At a minimum, community-engaged researchers should have an understanding of veteran history in relation to research, how veterans have experienced "volunteering" while under the chain of command, the impacts of a veteran's military experience, and veterans' views of the research process. The element most crucial to a successful research project conducted with the veteran community is incorporating veterans as full research team members. Building a veteran-centered research team requires academic researchers to establish trust with veteran team members and the veteran community, to conduct the research project with respect, and to actively encourage veterans' participation in project activities. All of these are facilitated by having veterans as full members of a research team. It is our hope that sharing the lessons we have learned through working with veteran communities, as well as our lived experiences as veteran research team members, will help pave a smoother path forward for others wishing to conduct impactful veteran-centered research.